Characterization of LIMA1 and its emerging roles and potential therapeutic prospects in cancers - Wang, Xiaoxiao; Zhang, Chao; Song, Huangqin; Yuan, Junlong; Zhang, Xiaomin; Yuan, Yiran; Zhang, Lei; He, Jiefeng (Frontiers in Oncology, 2023)
Actin is the most abundant and highly conserved cytoskeletal protein present in all eukaryotic cells. Remodeling of the actin cytoskeleton is controlled by a variety of actin-binding proteins that are extensively involved in biological processes such as cell motility and maintenance of cell shape. LIMA1, an important actin cytoskeletal regulator, was initially thought to be a tumor suppressor frequently downregulated in epithelial tumors. Importantly, LIMA1 deficiency may be responsible for dysregulated cytoskeletal dynamics, altered cell motility and disrupted cell-cell adhesion, which are thought to promote tumor proliferation, invasion and migration. As research progresses, the role of LIMA1 extends from cytoskeletal dynamics and cell motility to cell division, gene regulation, apical extrusion, angiogenesis, cellular metabolism and lipid metabolism. However, the expression of LIMA1 in malignant tumors and its mechanism of action have not been systematically elucidated, and still face many problems and challenges. Therefore, this review systematically describes the structure and biological function of LIMA1, and explores its expression and regulatory mechanism in malignant tumors, and further discusses its clinical value and therapeutic prospects.